Integrated transcriptome and microRNA profiles analysis reveals molecular mechanisms underlying the consecutive monoculture problem of Polygonatum odoratum - Chen, Yong; Liu, Zhi; Tu, Naimei; Hu, Yihong; Jin, Chenzhong; Luo, Yucai; Liu, Aiyu; Zhang, Xianwen (Cellular and Molecular Biology, 2020)
Polygonatum odoratum is a historically traditional Chinese medicine plant. However, the consecutive monoculture problem (CMP) widespread in other Chinese medicine limiting their cultivation on a large scale. In this study, the physiological data showed the adverse effect of CMP on the growth of P. odoratum under the consecutive cropping (CC) compared with the first cropping (FC). Then the high-throughput sequencing of miRNA and mRNA libraries of leaves and roots from FC and CC P. odoratum plants identified 671 differentially expressed genes (DEGs) and 184 differentially expressed miRNAs and revealed that the DEGs and target genes of the miRNAs were mainly involved in starch and sucrose metabolism, phenylpropanoid and brassinosteroid biosynthesis. The KEGG analysis revealed that the DEGs between CC and FC roots were enriched in the plant-pathogen interaction pathway. This study provided the expression regulation of genes related to CMP of P. odoratum but also suggested that CMP may result in the serious damage of pathogens to roots and cause the slow growth in the consecutive cropping plants.